Isolation and Purification of Oxalate Oxidase From Barley Seedling - Kapti Rahayu Kuswanto (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 1991)
A procedure of isolation of oxalate oxidase from barley seedling and a new method for purification is described. A purification step was accomplished by the second partition using polyethylene glycol (PEG-6000) and Devi-Iran-500 (4.5%1 4), and affinity chromatography using oxalate immobilized on activated CNBR-Sepharose 6MB as a ligand. After partition some protein were separated, and the specific activity were increased by 5-30 fold. The affinity chromatography using Oxalate-Sepharose effectively separated the oxalate oxidase. The specific activity of pure enzyme was 154.3 U/mg protein and the purity was 41 fold.